Pull-Up Crisp Container / Mohamad Firdaus Shaari ... [et al.] - Shaari, Mohamad Firdaus; Shamsudin, Kamarul Asyraf; Mohamad Azmi, Nurul Fatihah (2021)
Pull-Up Crisp Container is a product for introducing a new innovation for crisp container. This product created to make it easier for consumers to take food by eating it and crisp automatic push up from inside. The mission of Pull-Up Crisp Container is to produce a new version and ways of eating more hygiene for consumer use. The problem we get from this existing product is the way people want to eat crisp. For example, when user want drive while eat crisp to prevent sleepy, and when drive they difficult to grab crisp inside container. The innovator of Pull -Up Crisp Container is Kamarul Asyraf bin Shamsudin. Kamarul had been use this idea and creativity to create this innovation to attract supplier invest on our new product. He also has an experience with a moment of difficult to eating crisp which is easily broken, food becomes lethargic and difficult to store for a long time after the container is opened. This idea needed to be proposed to suppliers so that this innovation can be realized in market sector. This idea was pop-up when one of us started to create an easy way to take out crisp from a deep container. From there, we use method Research and Development (R&D) which is we use an existing crisp container and improve it with push up spring with stack make crisp are not sluggish and crispy which is we use double cover.